Why Rivals Intervene : International Security and Civil Conflict - Mitton, John (Book collections on Project MUSE., 2023)
"Rivals--states with acrimonious, militarized histories--often intervene on opposing sides of civil conflicts. These interventions are known to exacerbate and prolong civil wars, but scholars have yet to fully understand why states engage in them, given significant costs and countervailing strategic interests. Why Rivals Intervene argues that rivals are driven by security considerations at the international level--specifically, the prospect of future confrontations with their rival - to intervene in civil conflicts. Drawing on a theory of rivalry which accounts for this strategic rationale, John Mitton explores three case studies: Indian and Pakistani intervention in Afghanistan, Israeli and Syrian intervention in Lebanon, and US and Soviet intervention in Angola. The book examines a range of evidence, including declassified memoranda, meeting transcripts, government reports, published interviews, memoirs of political leaders, and other evidence of the thought process, rationale, and justifications of relevant decision-makers. The book claims that the imperatives for intervention are consistent across time and space, as rivals are conditioned by a history of conflict to worry about future confrontations. As a result, Why Rivals Intervene illuminates an important driver of civil conflict, with implications for how such conflicts might be solved or mitigated in the future. At the same time, it offers new insight into the nature of long-standing, acrimonious international relationships."--